math6a²b³-3a²b=?

2 answers

We can simplify the expression by factoring out the common factor of a²b:
math6a²b³ - 3a²b = 3a²b(a∙b² - 1)
AAAaannndd the bot gets it wrong yet again!

6a²b³ - 3a²b = 3a²b(2b² - 1)
Similar Questions
    1. answers icon 1 answer
    1. answers icon 3 answers
    1. answers icon 1 answer
  1. a) Find the product (1/2x2+y2) x-yb) Simplyfy 5/3a2b x (-3/4ab3) x (-4/5a2b2) and find the value for 2= -2 and b= 1. c) Divide x
    1. answers icon 1 answer
more similar questions